2019
DOI: 10.1111/jre.12649
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐like 4 production upon treatment with hypoxia and L‐mimosine in periodontal fibroblasts

Abstract: Background and objective A key factor in the modulation of angiogenesis as well as in bone resorption is angiopoietin‐like 4. However, the role of angiopoietin‐like 4 in periodontal tissue is unknown. Here, we hypothesized that hypoxia and the hypoxia mimetic agent L‐mimosine can induce the production of angiopoietin‐like 4 in periodontal fibroblasts. Methods Human periodontal ligament fibroblasts (PDLF) were cultured in monolayer and spheroid cultures. The cultures were incubated in the presence of hypoxia or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that ANGPTL4 is produced during inflammation. Although ANGPTL4 increases due to hypoxia in periodontal ligament fibroblasts, 14 the involvement and role of ANGPTL4 in periodontitis have not been elucidated. Ligature‐induced experimental periodontitis was used in a rat model of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ANGPTL4 is produced during inflammation. Although ANGPTL4 increases due to hypoxia in periodontal ligament fibroblasts, 14 the involvement and role of ANGPTL4 in periodontitis have not been elucidated. Ligature‐induced experimental periodontitis was used in a rat model of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that angiopoietin-like 4, an important signaling factor in modulation of angiogenesis, inflammation, lipid metabolism, and bone resorption, is induced by HIF-1 in human periodontal ligament fibroblasts and it can also be modulated by P. gingivalis LPS, IL-1 and TNF-α [103]. Although the function of angiopoietin-like-4 in periodontal tissues is not yet fully known, its mediation of angiogenesis and bone regeneration in inflammation, especially under hypoxic conditions, indicates that it may stand out as a good therapeutic agent candidate for periodontal diseases.…”
Section: Hypoxia In Local Inflammationmentioning
confidence: 99%
“…United States), DS-1093 (Daiichi Sankyo, Inc., Chuo City, Tokyo, Japan, no longer investigated for anemia) and Zyan1 (Cadila Healthcare Ltd., Ahmedabad, Gujarat, India) are still in preclinical, phase 1 or 2 clinical trials for renal anemia or are being evaluated for other indications. Other HIF-PHIs such as dimethyloxalylglycine ( Trichonas et al, 2013 ; Xie et al, 2014 ), L-mimosine (L-mim) ( Trimmel et al, 2015 ; Janjic et al, 2019 ), MK8617 ( Debenham et al, 2016 ; Li et al, 2019 ) and an FIH selective inhibitor N-oxalyl-D-phenylalanine ( Meng et al, 2018 ) are still in preclinical research. Since the action and mechanism of HIF-PHIs in CKD anemia are well summarized in reviews published before ( Forristal and Levesque, 2014 ; Gupta and Wish, 2017 ; Haase, 2017 ; Locatelli et al, 2017 ; Del Vecchio and Locatelli, 2018 ; Sanghani and Haase, 2019 ), this article focuses on milestones in the development of these clinical available HIF-PHIs and their potential in treating non-anemic diseases.…”
Section: Introductionmentioning
confidence: 99%